The effect of electron characteristics on the optimum transport into the dense pre-plasma for fast-shock ignition concept - S.A. Ghasemi; S. Faghih; B. Khanbabaei (مجله علوم و فنون هسته‌ای, 2020)
In this paper, the effect of the initial electron energy with E0=1-10 MeV, its distribution function and pre-plasma background temperature T=0.5-10 keV on the optimum transport into the dense fuel with the density ρc=292-828 g.cm-3 have been investigated analytically for fast-shock ignition concept. The analytical results showed that for Te ≥ 5 keV, the Coulomb logarithm of the charged particle is weakly dependent on the pre-plasma temperature, and it seems that the plasma stopping power is approximately independent of background temperature. Therefore, it could be concluded that pre-plasma temperature is not a key parameter for the electron penetration improvement, and the electron penetration can be optimized by a decrement of fuel density and increment of electron incident energy; in a way that the optimal condition obtained about E0≈4.5 MeV for electron incident energy and ρc=300 g.cm-3 for pre-plasma density. Furthermore, investigating the impact of the fast ignitor wavelength and electron energy distribution function showed that the electron distribution function is almost independent of the background temperature and by considering quasi two-temperature distribution function for electron and fast ignitor wavelength λif ≈ 0.35 µm, the optimized penetration may be obtained. The analytical results showed an acceptable agreement with those of Monte Carlo simulations.